Litho-stratigraphic Study and Morphodynamic Implications of the Plio-Quaternary Deposits in the Sabadia Area, Central Rif, Morocco - Moqaddem Achraf; Azzouz Omar; Makkaoui Mohamed; Bouiss Hanae; Bengamra Said (E3S Web of Conferences)
The coastal zones of the central Rif are marked by a segmented alignment of maritime cliffs, coinciding with the regional faults that structure the Bokoya Massif. The morpho-structural examination shows that the shaping of these steep reliefs is dictated by recent deformations, marked by tilting toward the North, associated with the collapse of the Alboran Sea. The characterization of this coastal dynamic is studied based solely on the remnants of marine and continental terraces that persist in the northern central part, at the level of Sabadia (Al Hoceima Sector). Stratigraphic examination shows that these terraces are organized into three distinct regressive sequences, with variable thicknesses and extensions, delimited at their base by well-marked erosion surfaces. The partial superposition of these sets is part of an evolutionary regressive process, ranging from a distinctly marine environment to purely continental deposits. The geometry of their deposits is respectively controlled by phenomena of relative tilting, with different attitudes, corresponding to three episodes of brittle deformations.